STUDI PERBANDINGAN PARADIGMA FUNGSIONALISME STRUKTURAL VS STRUKTURALISME LEVI-STRAUSS - Devi, Intan Sari (P3M IAIN KEDIRI, 2018)
This study aims to compare two paradigm functional paradigm (structural) vs. structuralism Levi-Strauss. To answer questions about both these paradigms will use a comparative study between functionalism paradigm theory or functionalism (structural) and developed structuralism Levi-Strauss as well as how both of these paradigms looking at a structure in understanding the symptoms of socio-cultural community. In the discussion of this study describes each paradigm in accordance with the basic assumptions, models, concepts and how each of these paradigms that analyze the social phenomena of culture in society by means of analysis of different fungsionalisme- (structural ) considers language as all that exists in the community has a social function and integrate with each other structurally, but developed structuralism Levi-Strauss understand the socio-cultural phenomenon kinship system, mythology and socio-cultural issues that exist in society as a structure of the language.